A neoteric approach to achieve BaF2:Yb3+, Er3+ one-dimensional nanostructures with color-tuned up-conversion luminescence. Issue 23 (1st December 2022) - Li, Ning; Shao, Hong; Qi, Haina; Yang, Liu; Sheng, Yuqi; Xie, Yunrui; Li, Dan; Yu, Wensheng; Ma, Qianli; Dong, Xiangting
Abstract: One-dimensional (1D) nanostructures have received considerable attention owing to their peculiar traits and extensive applications. Alkaline-earth metal fluorides are favorable substrates for rare earth ions luminescence. Most of the rare-earth-doped alkaline-earth metal fluorides nanomaterials obtained by current methods are in the form of nanoparticles without one-dimensional nanostructures. Therefore, the convenient and quick preparation of rare-earth-doped alkaline-earth metal fluorides 1D nanostructures has become an important topic of study. In this work, BaF2 :Yb 3+, Er 3+ up-conversion luminescence (UCL) 1D nanostructures, as a case study, have been designed and constructed via recently proposed mono-axis electrospinning united with dual-crucible fluorating technology. Controllable fabrications of BaF2 :Yb 3+, Er 3+ nanofibers, nanobelts and hollow nanofibers 1D nanostructures are successfully and facilely realized via simply regulating the compositions and ratios of the electrospinning solutions by applying the above technique. The effects of morphology, calcination temperature and molar ratios of Yb 3+ to Er 3+ on the UCL characteristics of the samples are systematically investigated, and color-tuned up-conversion luminescence is achieved. It is found that as-obtained pure cubic-phase BaF2 :Yb 3+, Er 3+ 1D nanostructures display excellent UCL properties under the 980-nm laser excitation, and the intensity of green emission ( 2 H11/2 → 4 I15/2 and 4 S3/2 → 4 I15/2 ) is greater than that of red emission ( 4 F9/2 → 4 I15/2 ), leading to superior green fluorescence. Further, the BaF2 :Yb 3+, Er 3+ nanofibers have the strongest fluorescence intensity of the three kinds of morphological samples, realizing modulation of luminous intensity via regulation of morphologies. The detailed luminescent mechanisms of the samples are advanced. The fabrication techniques are established and the formative mechanisms of the 1D nanostructures are detailedly elaborated. More notably, the proposed design concept and preparation technique can be extended to manufacture other metallic fluorides 1D nanomaterials. Graphical abstract: Image 1 Highlights: A new scheme is designed to construct BaF2 :Yb 3+, Er 3+ one-dimensional nanostructures. Regulation of 1D morphologies is easily realized via modulating spinning parameters. BaF2 :Yb 3+, Er 3+ 1D nanostructures display superior green up-conversion fluorescence. Luminous colors can be tuned by regulating the ratio of Yb 3+ to Er 3+ and morphology. Formative mechanisms of the nanofiber, hollow nanofiber and nanobelt are elucidated.